Assessing the Energy Subsidy Reform in Indonesia through Different Scenarios - Murjani, Ahmadi (International Journal of Energy Economics and Policy, 2020)
This paper provides a comprehensive study on energy subsidy reform simulations in Indonesia by employing two new approaches, namely, the Almost-Ideal Demand System Iterated Linear Least-Square and SUBSIM. Periods of low and high oil prices are also accounted in this paper; further, it reveals that in 1999, when oil prices were low, this reform was possible due to Indonesia’s status as a net oil exporter and precise selected-reformed energy goods; however, the major concerns were the unsupporting welfare situations and the depreciation of the rupiah after the Asian Financial Crisis in 1997. In 2012, the evidence shows that despite high oil prices and Indonesia being a net oil importer, this reform saved more for the government and made significant welfare impacts. Overall, this paper suggests that this reform is feasible when at least some factors, i.e., stable national exchange rate, conducive welfare situations, availability of potential recipients’ database, and functioning government, are well-established. Keywords: Almost-Ideal Demand System; Energy goods; Simulation; Subsidy reform; Indonesia. JEL Classifications: D12, H53, I38, Q48 DOI: https://doi.org/10.32479/ijeep.9223